A comparison of the growth and survival of two freshwater crayfish species, Astacus leptodactylus Eschscholtz and Pacifastacus leniusculus (Dana), under different temperature and density regimes - Harlioglu, Muzaffer Mustafa (Springer, 2009)
Growth experiments carried out with two juvenile crayfish species, Astacus leptodactylus Eschscholtz and Pacifastacus leniusculus (Dana), at different temperatures and densities highlighted the problem of cannibalism under conditions aimed at intensifying crayfish production. Cannibalism proved to be much lower in A. leptodactylus than P. leniusculus, suggesting that the former might be the better candidate for astaciculture. In the first of two population survival trials, A. leptodactylus showed a higher survival rate than P. leniusculus, with 26% of P. leniusculus surviving in the first replicate, compared to 42.3% of P. leniusculus, and 40.76% surviving in the second replicate, compared to 47.6% of P. leniusculus. The same trend was observed in the second experiment, with P. leniusculus showing survival rates of 48.5 and 55.3% (first and second replicates, respectively) in comparison to 65.2 and 68.2%, respectively, for A. leptodactylus. It is therefore highly likely that if P. leniusculus were to become established in Turkey, it would outcompete the native A. leptodactylus even if it were not to be devastated by the crayfish plague that has decimated the native species. The experiments also highlighted the problem of differential growth, with some juveniles hardly growing at all while others reached a relatively large size. The range in carapace length (CL) was 9-18 mm for A. leptodactylus and 8.5-18.5 mm CL for P. leniusculus at the end of the first experiment. While both species grew quickly, P. leniusculus hatched earlier, giving it an advantage over A. leptodactylus; consequently, by the end of the summer, the juveniles of the former were larger than those of A. leptodactylus. Specific growth rate values showed that the juveniles of the two species had similar growth rates. The results also revealed that growth was not significantly affected by density in both species at 15A degrees C, but at 25A degrees C, growth was significantly better at a density of 234 juveniles m(-2) than at 468 juveniles m(-2), and better at 468 juveniles m(-2) than at 937 juveniles m(-2) (P < 0.01 and P < 0.001, respectively). We conclude that P. leniusculus is a good candidate for aquaculture as it has a rapid growth rate and early hatching and maturity; however, its aggressive behavior may make it a less attractive proposition than A. leptodactylus, which is also fast growing but less aggressive.
Keywords: Astacus leptodactylus; Crayfish; Growth; Juvenile; Pacifastacus leniusculus; Survival